Indonesian Rice Farm Households' Perceived Effect of COVID-19 Pandemic - Zaura Fadhliani; Irham Irham (Universitas Muhammadiyah Jember, 2022)
Rice is one of the most significant commodities in Indonesian agricultural sector and it is also the largest employer in rural areas. The majority of rice farmers fall into the category of subsistence farmers, who engage in agricultural production not just for commercial goals but also to meet domestic demand for food. The aims of this study is to understand the scope of the COVID-19 pandemic's influence on rice farmers and production. By utilizing a questionnaire, we descriptively present the socio-economic characteristics of 80 rice farmers in Kulon Progo Regency. The likert scale is used to elicit the perceived effect of the COVID-19 pandemic on the rice farmers. According to the findings, most rice farmers are poor and vulnerable to the effects of the COVID-19 pandemic. The coronary disease outbreak negatively impacts rice farm households by affecting farmers' health, reducing sales, limiting the ability to replant, decreasing agricultural input availability, lowering household income, and limiting primary food access. On the other hand, the majority of respondents in this study state that there is no labor scarcity on the farm during the outbreak due to employing the family members to labor on the fields.